Digital Learning Resources: Pre-service English Teachers' Viewpoints in Southwest Maluku Archipelago - Kamanasa, Louisa Sarah; Keiwury, Erna Lisna; Mose, Ningsi (Program Studi Pendidikan Bahasa Inggris Kabupaten Kepulauan Aru, 2024)
The integration of digital learning tools in language teaching has gained great popularity in recent years, particularly within the context of the Era 5.0, which emphasizes the amicable relationship between humans and technology. This study explores the viewpoints of pre-service English teachers regarding the implementation and effectiveness of digital learning resources in language teaching and acquisition. By employing mixed-method research, the data gathered through a 5-Likert scale questionnaire and semi-structured interview. The study aims to uncover the perceptions, experiences, and attitudes of these future language educators toward the use of digital tools and platforms in their classrooms. The result showed that all students have positive attitudes towards the use of technology in language learning especially in preparing learning material. However, professional development in preparing the pre-service English teacher in real-life experience as a teacher in school to be tech-savvy is needed. This study also suggests integrating technology into extracurricular activities and embedding digital literacy within the curriculum to better prepare students for the future